2014
DOI: 10.1056/nejmoa1303657
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Childhood Tuberculosis and Host RNA Expression in Africa

Abstract: BACKGROUND Improved diagnostic tests for tuberculosis in children are needed. We hypothesized that transcriptional signatures of host blood could be used to distinguish tuberculosis from other diseases in African children who either were or were not infected with the human immunodeficiency virus (HIV). METHODS The study population comprised prospective cohorts of children who were undergoing evaluation for suspected tuberculosis in South Africa (655 children), Malawi (701 children), and Kenya (1599 children)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
326
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 326 publications
(344 citation statements)
references
References 32 publications
6
326
0
6
Order By: Relevance
“…A disease risk score was developed that can now be developed into a simple test format suitable for use in HIV-infected TB populations. A more recent study extended this work also to TB-infected infants, with similar results in terms of the identification of useful diagnostic TB disease mRNA biosignature (Anderson et al 2014). Prospective studies using such tests are now needed to validate their actual performance.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 63%
“…A disease risk score was developed that can now be developed into a simple test format suitable for use in HIV-infected TB populations. A more recent study extended this work also to TB-infected infants, with similar results in terms of the identification of useful diagnostic TB disease mRNA biosignature (Anderson et al 2014). Prospective studies using such tests are now needed to validate their actual performance.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 63%
“…Selected sets of mRNA transcripts have been used in prediction models to classify patient samples as having active TB or not (5)(6)(7)(8)(9)(10)(11). In early phase studies (12), blood transcriptional classifiers have shown promise for active TB diagnosis (3,10,11,13,14) and for monitoring treatment response (15).…”
mentioning
confidence: 99%
“…Recent advances in systems biology and computational biology have created new opportunities. For example, gene-expression analysis has been used to differentiate active pulmonary tuberculosis from both latent tuberculosis and nontuberculous disease (36)(37)(38). Test characteristics were superior to currently available pathogen-detection techniques.…”
Section: Discussionmentioning
confidence: 99%